2019
DOI: 10.1101/853622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spexin and a novel cichlid-specific spexin paralog both inhibit FSH and LH through a specific galanin receptor (Galr2b) in tilapia

Abstract: 21Spexin (SPX) is a 14 amino acid peptide hormone that has pleiotropic functions 22 across vertebrates, one of which is involvement in the brain-pituitary-gonad axis of fish. 23 SPX(1) has been identified in each class of vertebrates, and a second SPX (named SPX2) 24 has been found in some non-mammalian species. We have cloned two spexin paralogs, 25 designated as Spx1a and Spx1b, from Nile tilapia (Oreochromis niloticus) that have 26 varying tissue distribution patterns. Spx1b is a novel peptide only… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 50 publications
(1 reference statement)
0
11
1
Order By: Relevance
“…However, in a study with grouper fishes, SPX treatment does not affect mRNA expression of LH and FSH in the pituitary (7). Contrary to this data, there are studies showing that SPX can inhibit LH and FSH secretion (9,20,22). In another study, the effect of SPX on gamete maturation and puberty onset was investigated, and it was reported that SPX knockout zebrafish has fertility without abnormality in the timing of pubertal onset or gamete maturation in the testes and ovary (55).…”
Section: Reproductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, in a study with grouper fishes, SPX treatment does not affect mRNA expression of LH and FSH in the pituitary (7). Contrary to this data, there are studies showing that SPX can inhibit LH and FSH secretion (9,20,22). In another study, the effect of SPX on gamete maturation and puberty onset was investigated, and it was reported that SPX knockout zebrafish has fertility without abnormality in the timing of pubertal onset or gamete maturation in the testes and ovary (55).…”
Section: Reproductionmentioning
confidence: 88%
“…The widespread synthesis of SPX has pointed out that it regulates many physiological functions in the body. For instance, SPX affects food intake (6)(7)(8)(9)(10)25) glucose/fat metabolism (11)(12)(13)(14)(15) gastrointestinal motility (1,16), pain perception (5,17,18), endocrine (10,12,(19)(20)(21), reproductive (7,10,20,(22)(23)(24) and cardiovascular functions (17). Additionally, the important roles of SPX have been revealed in pathological conditions such as obesity, anorexia nervosa, diabetes, anxiety, and depression (26)(27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…The mature peptide sequence, NWTPQAMLYLKGAQ‐NH 2 , is flanked by RR/KR and GRR dibasic proteolytic cleavage sites, and it is identical in all tetrapods studied so far (Lv et al., 2019; Mirabeau et al., 2007; Sonmez et al., 2009), except in panda, dog, and cat with a substitution of Ala 6 to Ser 6 . In fish, Spx orthologs differ from mammalian and avian forms in only one amino acid, an Ala 13 to Thr 13 , a substitution that is present in all species investigated to date (Cohen et al., 2020; Lim et al., 2019; Ma et al., 2018). Recently, another paralogous form of Spx, called Spx2, has been identified in a few non‐mammalian species (D. K. Kim et al., 2014), and hence the initial mature Spx was termed Spx1.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another paralogous form of Spx, called Spx2, has been identified in a few non‐mammalian species (D. K. Kim et al., 2014), and hence the initial mature Spx was termed Spx1. It is worth mentioning that two Spx1 paralogs, designated as Spx1a and Spx1b, were found in Nile tilapia, while Spx2 is absent in this species (Cohen et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While most of the significant factors along the HPG axis are conserved between mammals and teleost [4, 5], little is known about the mechanisms that regulate GnRH activity and its direct control on gonadotrophs. While various neuropeptides have been suggested to interact in the regulation of GtH secretion, such as kisspeptin [6, 7], neurokinin B and F [8, 9], GnIH [8], and spexin [10], how they interact with the different components of the HPG axis remains unknown. An additional important component of the HPG axis is the feedback regulation of sex steroids (testosterone [T] and estradiol [E 2 ]) on the brain and the pituitary.…”
Section: Introductionmentioning
confidence: 99%